Psychosocial Factors and Organizational Commitment among Female Generation Z Employees in the Manufacturing Sector: The Mediating Role of Job Satisfaction - Fariha Azzahra; Indah Rahayu; Rosmala Kurnia Dewi; Wahyu Hermawan (Greenation International Journal of Economics and Accounting, 2026)
The manufacturing sector plays a strategic role in Indonesia’s economy and serves as a major employer for Generation Z workers. However, female Generation Z employees in manufacturing often face high work pressure, physical demands, and psychological challenges that may reduce job satisfaction and organizational commitment. This study aims to examine the influence of mental toughness and person–organization fit on organizational commitment through job satisfaction. A quantitative approach was employed using survey data collected from 160 female Generation Z employees in manufacturing companies in Grobogan Regency. The data were analyzed using Partial Least Squares (PLS). The results indicate that mental toughness and person–organization fit have a positive and significant effect on job satisfaction. Job satisfaction also has a significant positive effect on organizational commitment and mediates the relationship between mental toughness, person–organization fit, and organizational commitment. Person–organization fit was found to be the strongest predictor of job satisfaction. These findings suggest that strengthening mental resilience and aligning individual and organizational values are essential to enhance job satisfaction and commitment. Therefore, organizations are encouraged to integrate mental toughness development and person organization fit strategies into human resource management practices to reduce turnover and support sustainable workforce retention.